Oryginalność zwielokrotniona. Autocytaty w wybranych powieściach Stanisława Lema - Mazurkiewicz, Adam (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
The article shows the description of intcrtextual present in late S. Lems novels. It might be called ‘auto-inter-textualitation’. Three modern novels of Lem ("Local vision”, "Fiasco” and “Peace on the Earth") contains the references to his previous pieces of work. The heroes from the previous novels and their sentences or even fragments, which had been selected from the previous stories, are now beeing appeared in the other context with new meanings (sometimes totally different than before).